The impacts of new traffic signs provision on road safety levels in higher educational campus infrastructure provision and renovation - Sahrir, Syazwani; Bachok, Syahriah; Mohamed Osman, Mariana (2011)
This paper deals with the effectiveness of traffic signs provision in International Islamic University Malaysia (IIUM), Gombak campus, a case study selected to represent an international campus environment. The provision of traffic signs gives, to a certain extent, an impact to road safety levels in campuses. Literature has found that the effectiveness of any sign depends upon its attention, meaning, time, respect values and illumination. 100 questionnaire forms have been distributed; only 64 have been analyzed after the data cleaning. The 64 forms were completed by the students who registered their car with the campus Traffic Unit. Findings show that a sign must attract the visual attention of the driver at a range greater than the reading distance requirement. It was also found that gender was the factor that influenced the perceptions of the respondents towards the effectiveness of the colour and illumination of traffic signs. In addition, the frequency of signage observation, to a limited extent, influenced the perceptions of respondents toward the effectiveness of the font size of traffic signs. Therefore, it is suggested that, the sign must appear reasonable, rational, and advantageous to the road users. The visual attention, sign lettering and legibility, maintenance and illumination of traffic signs, in the campus, need to be improved in the future. Keywords: Traffic sign, effectiveness of sign, campus planning, student drivers